Óxido de zinco dopado para produção de biodiesel - Pereira, Maria de Fatima (2016)
Powders of pure zinc oxide (ZnO) and zinc oxide doped with 5% Al3+ (ZNAL) were obtained by the Pechini method using Zn(NO3)2.6H2O and Al(NO3)3.6H2O as precursors. The characterization was performed using XRD, Raman, FTIR and UV-Vis, and stoichiometry was confirmed by XRF. The results obtained by Raman and XRD indicated that Al3+ is completely incorporated into the ZnO crystal lattice. Attempts of doping ZnO with Fe3+ lead to a secondary phase which, according to ICCD 01-070-3377, was assigned to ZnFe2O4, for this reason this oxide was not used as a catalyst. Tests of pH variation with the oxides in acidic and basic media indicated that ZNAL presents a much larger basic character than ZnO. Using a 23 factorial design, ZnO and ZNAL were tested as catalysts for the ethanolic transesterification of cottonseed oil at temperature 130 and 200 °C, alcohol/oil ratio of 6:1 and 12:1 and 3% catalyst (w/w relative to the oil ). The reactions were performed in the Parr reactor for 4 hours and agitation of 600 rpm. 1H NMR and 13C NMR spectroscopies were used to characterize and evaluate the ethyl ester content produced during transesterifications indicating that 5% of Al3+ addition into the crystalline ZnO lattice significantly increased the catalytic potential of the oxide, reaching a higher conversion ratio of 81% when T = 130 °C and greater than 94% when T = 200 °C. The results analyzed by factorial design indicated that the type of catalyst and the temperature were the most determining factors in conversion rates. Using a kinetic study at temperatures of 130, 160, 180 and 200 °C and reaction times of 30, 60, 120 and 240 minutes, it was observed that the reactions catalyzed by ZnO had a linear behavior conversion rate, while reaction catalyzed by ZNAL reached rates greater than 80%of conversion after 30 minutes when T = 200 °C. It was also observed that the rate of ethanolic transesterification of cottonsed oil was influenced by mass transport phenomena when catalyzed by ZnO. For transesterifications catalysed by ZNAL a 1st order behavior was observed at T = 130 ° C and 2nd order was observed for the other temperatures.